In–out impurity density asymmetry due to the Coriolis force in a rotating tokamak plasma. (5th September 2018) - Pan, Chengkang; Wang, Shaojie; Xiao, Xiaotao; Ye, Lei; Xu, Yingfeng; Dai, Zongliang
Abstract: The effect of the Coriolis force due to the impurity toroidal and poloidal rotation on the in–out impurity density asymmetry in a rotating tokamak plasma is investigated. The role of the Coriolis force is figured out explicitly in the toroidally rotating plasma frame. The in–out impurity density asymmetry can be induced by the Coriolis force with, in this case, when moving along the magnetic field line from the outboard side to the inboard side in a magnetic flux surface, one sees a positive Coriolis force. The combined effects of the centrifugal force, the Coriolis force, the poloidal electric field and the ion-impurity friction force on the in–out impurity density asymmetry are discussed. The proposed theoretical model can be applied to improve the understanding of the in–out impurity density asymmetry observed in the tokamak experiments.